Livestock landscapes as ecological filters: Effects of the tree cover gradient on the taxonomic and functional diversity of granivorous birds in the Colombian Amazon - Jenniffer Tatiana Díaz-Cháux; Alexander Velasquez-Valencia; Alejandro Navarro-Morales; Fernando Casanoves (PLoS ONE, 2026)
Land-use intensification in cattle-ranching landscapes of the Colombian Amazon generates continuous gradients of tree cover that modify the structure of productive mosaics and may function as environmental filters. The effects of this gradient may vary depending on the biodiversity component and the scale of analysis considered. We evaluated how tree cover is associated with the abundance, taxonomic richness, and functional diversity of the granivorous bird guild in cattle-ranching landscapes of the Colombian Amazon. A total of 100 quadrats were sampled along the continuous tree cover gradient. Abundance and local richness were analyzed using generalized linear mixed models with a negative binomial distribution. Taxonomic diversity pooled by cover type was estimated using Hill numbers with explicit control of sampling completeness. Functional structure was assessed using multidimensional indices (FRic, FEve, FDiv, FDis, and RaoQ) and multivariate trait-based analyses (RLQ and fourth-corner tests). Tree cover had a significant effect on local abundance, whereas quadrat-level richness showed only a marginal response. Taxonomic diversity was higher in structurally more heterogeneous covers, consistent with greater spatial turnover. At the functional level, FDis and RaoQ varied among covers, whereas FRic and FEve did not differ significantly. RLQ analysis identified significant covariation between proportions of tree cover and traits associated with body size and bill and tarsus morphology in granivorous birds. Overall, the results describe a partial and scale-dependent reorganization of the granivorous assemblage along the structural gradient. Although consistent with theoretical expectations of environmental filtering, these patterns should be interpreted as observational associations rather than causal evidence or direct evaluations of ecosystem functions.